Direitos humanos, violência doméstica e familiar um estudo de caso na delegacia especializada de atendimento as mulheres em Teresina - PI - Oliveira, Carliane Ribeiro de (2023)
The present research is based on theories of several authors, such as Sánchez Romero, Álvarez, Saffioti, Bandeira, Almeida, Passinato, Santos and others, which address issues such as gender violence, patriarchy, women's human rights and legislation for the defense of women's rights in Brazil. The general objective of this research is to analyze violence against women in the light of human rights, focusing on the performance of the Specialized Police Station for Women's Assistance (DEAM) in the city of Teresina, Piauí. As for the methodology, the study is qualitative in nature and involves data collection through interviews with 20 women at the DEAM in Teresina, PI. In addition, records of observations at the police station, literature review and bibliography on the subject will be used. The research is characterized as a case study, aiming to deepen the understanding of the specific aspects of the Teresina DEAM in relation to Human Rights. The results revealed the challenges and advances in the fight against this problem, highlighting the importance of the human rights of women victims of violence in the construction of a fairer society. The police station's analysis highlighted its multidisciplinary and sensitive approach, which is fundamental in protecting victims and raising public awareness. The victims are predominantly white, with educational backgrounds and children, although there are cases of greater social vulnerability. The Maria da Penha Law has been shown to be effective in the DEAM, providing specific procedures and referral to support networks.